HLA alleles and HLA‐B27 haplotypes associated with susceptibility and severity of ankylosing spondylitis in a Portuguese population. Issue 6 (December 2013) - Pimentel‐Santos, F. M.; Matos, M.; Ligeiro, D.; Mourão, A. F.; Ribeiro, C.; Costa, J.; Santos, H.; Barcelos, A.; Pinto, P.; Cruz, M.; Sousa, E.; Santos, R. A.; et al.
Abstract Human leukocyte antigen (HLA)‐B27 is the mostly known major histocompatibility complex (MHC) gene associated with ankylosing spondylitis (AS). Nonetheless, there is substantial evidence that other MHC genes appear to be associated with the disease, although it has not yet been established whether these associations are driven by direct associations or by linkage disequilibrium (LD) mechanisms. We aimed to investigate the contributions of HLA class I and II alleles and B27‐haplotypes for AS in a case–control study. A total of 188 HLA‐B27 AS cases and 189 HLA‐B27 healthy controls were selected and typed for HLA class I and II by the Luminex polymerase chain reaction‐sequence specific oligonucleotide probe (PCR‐SSOP) method. Allelic and haplotypic distributions were estimated by maximum likelihood method using Arlequin v3.11 and statistical analysis were performed by Stata10.1. No associations were found between non‐HLA‐B27 loci and AS susceptibility, but several associations were observed for phenotypic features of the disease. DRB1*08 was identified as a risk factor for uveitis and DQB1*04 seems to provide protection for AS severity (functional, metrological and radiological indexes). A*02/B27/C*02/DRB1*01/DQB1*05 [P<0.0001; odds ratio (OR) = 39.06; 95% confidence interval (CI) (2.34–651)] is the only haplotype that seems to confer susceptibility to AS. Moreover, the haplotype A*02/B27/C*01/DRB1*08/DQB1*04 seems to provide protection for disease functional and radiological repercussions. Our findings are compatible with the hypothesis that other genes within the HLA region besides HLA‐B27 might play some role in AS susceptibility and severity.